The Effectiveness of Education Through Peer Groups on Increasing Knowledge, Attitudes and Implementation of Balanced Nutrition in Preventing Anemia : (In Adolescent Girls at SMPN 1 Paringin) - Siti Nurhayani,; Fatimah Fatimah, (International Journal Of Health Science, 2025)
Adolescence is a crucial period in the human life cycle for improving the Human Development Index. Growth during adolescence is more rapid than in previous periods, resulting in increased nutritional needs. Rapid growth and high activity levels in adolescents can impact nutritional needs. Therefore, adolescents, especially adolescent girls, are a group that is vulnerable to nutritional problems, including anemia and KEK.These problems in girls are closely related to stunting. This study aims to determine the effectiveness of peer group education on improving knowledge, attitudes, and the application of balanced nutrition in preventing anemia in adolescent girls. The research method used a quasi-experimental non-equivalent control group design. The sample size was 62 people. The sampling technique used purposive sampling. The data obtained were then analyzed using paired t-test statistics and Wilcoxon for paired difference tests. The results showed that the overall p-value obtained was <0.05, indicating a difference before and after the intervention in improving knowledge, attitudes, and the application of balanced nutrition in preventing anemia. Peer Group Education is effective in improving knowledge, attitudes, and the application of balanced nutrition in preventing anemia in adolescent girls.